The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1183/16000617.0085-2015
|View full text |Cite
|
Sign up to set email alerts
|

The role of moxifloxacin in tuberculosis therapy

Abstract: Tuberculosis (TB) remains a global threat with more than 9 million new infections. Treatment remains difficult and there has been no change in the duration of the standard regimen since the early 1980s. Moreover, many patients are unable to tolerate this treatment and discontinue therapy, increasing the risk of resistance. There is a growing tide of multidrug resistance and few effective antibiotics to tackle the problem. Since the turn of the millennium there has been a surge in interest in developing new the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 77 publications
2
47
0
2
Order By: Relevance
“…Some among the above-cited compounds have novel mechanisms of action and can kill antibiotic-resistant strains (6)(7)(8)(9), although clinical trials with moxifloxacin were disappointing (10). A growing pipeline of anti-TB compounds is also under development or undergoing clinical trials, and these experimental compounds are anticipated to improve treatment outcomes (11).…”
mentioning
confidence: 99%
“…Some among the above-cited compounds have novel mechanisms of action and can kill antibiotic-resistant strains (6)(7)(8)(9), although clinical trials with moxifloxacin were disappointing (10). A growing pipeline of anti-TB compounds is also under development or undergoing clinical trials, and these experimental compounds are anticipated to improve treatment outcomes (11).…”
mentioning
confidence: 99%
“…Because quinolone resistance generally develops against a common part of the drug group, cross-resistance is frequently observed among quinolones (12-14). However, minimum inhibitor concentrations (MIC) of the new quinolones are lower compared to those of Pulmonologist (n=1), 3 Internal Medicine (n=1), 3 Emergency Physician (n=1) ARB: Acid-resistant bacilli; m±SD: mean±standard deviation; TB: tuberculosis the old quinolones. Therefore, the new quinolones may be effective on bacteria resistant to old quinolones such as ofloxacin (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…At present, quinolones are routinely used in the treatment of multi-drug resistant tuberculosis (MDR-TB). In a recently published review, it has been reported that moxifloxacin is as bactericidal as first-generation tuberculosis drugs and this drug should be used in the treatment of MDR-TB routinely and it should be among the first choices for patients that can not tolerate standard treatment (3). There are ongoing studies on the inclusion of moxifloxacin in the standard treatment for shortening the duration of treatment (4-6).…”
Section: Introductionmentioning
confidence: 99%
“…Nowe generacje fluorochinolonów zostały umieszczone w zaleceniach, a ich skuteczność w leczeniu MDR-TB wynika z faktu, iż ta grupa leków cechuje się większą penetracją do wnętrza makrofagów niż ofloksacyna czy cyprofloksacyna [64,65]. Określając wartość MIC dostępnych fluorochinolonów w stosunku do prątka gruź-licy, wykazano duże zróżnicowanie zależne od obecności grupy metoksylowej w pozycji C8 [66,67]. Zwrócono jednak uwagę na fakt, że fluorochinolony ze znaczną aktywnością przeciwbakteryjną ujawniały zbyt dużo działań ubocznych, niekiedy toksycznych, np.…”
Section: Fluorochinolony W Leczeniu Gruźlicyunclassified
“…Aktualnie -zgodnie ze wskazaniami WHO -do leczenia chorych na MDR-TB rekomendowane są lewofloksacyna i moksyfloksacyna [64,66,70,71]. Potwierdza to w pełni metaanaliza 6465 przypadków chorych na gruźlicę, w której porównywano skuteczność m.in.…”
Section: Fluorochinolony W Leczeniu Gruźlicyunclassified